Online Review Analysis TriggeringHype in the Motion Picture Industry - Timothy Rey Laheba; Paulus Wisnu Anggoro (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2021)
Competition in the motion picture industry continues to intensify at a very rapid pace. This phenomenon makes the production house continue to try to look for new ways to maximize revenue from the short life cycle of a film. One of the variables currently playing a larger role in decision-making to watch a film is a review. Two types of reviews are often used in the motion picture industry, namely the reviews from critics and fellow consumers. This study tries to see whose review will trigger a hype or buzz that much needed in the motion picture industry. Data from 219 respondents were collected to see their response regarding a review and whose review will encourage them to talk about a film to their peers and ultimately create the hype needed by a film. There are different perceptions for reviews given by critics, and fellow consumers with reviews from fellow consumers have greater potential to create and ignite hype in the motion picture industry.